1982
DOI: 10.1128/iai.38.1.325-342.1982
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of phagosomes containing Chlamydia psittaci from L cells

Abstract: The obligate intracellular procaryote Chlamydia psittaci enters host cells by a mechanism similar to, but distinct from, conventional phagocytosis. To better understand chlamydial uptake, L-cell phagosomes containing a single chlamydial cell were isolated and studied. Two rounds of dextran rate-zonal gradient centrifugation of L cells homogenized 1 h after infection with C. psittaci yielded phagosomes relatively free of other membranous structures. In double-label experiments, the phagosomes were enriched over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…More than two decades ago, Friis (1972) was the ®rst to conclude that phagosomes harbouring C. psittaci do not fuse with lysosomes within L cells. This notion was supported by several subsequent experiments performed mainly on macrophages infected with the same species (Wyrick and Brownridge, 1978;Zeichner, 1982;1983). Similarly, more recent studies on the traf®cking routes of C. psittaci or C. trachomatis in the target epithelial cells have pointed to a complete disconnection of chlamydial inclusions from the endocytic pathway and the lack of phagosomal acidi®cation (Heinzen et al, 1996;Schramm et al, 1996;Taraska et al, 1996).…”
Section: Introductionmentioning
confidence: 74%
“…More than two decades ago, Friis (1972) was the ®rst to conclude that phagosomes harbouring C. psittaci do not fuse with lysosomes within L cells. This notion was supported by several subsequent experiments performed mainly on macrophages infected with the same species (Wyrick and Brownridge, 1978;Zeichner, 1982;1983). Similarly, more recent studies on the traf®cking routes of C. psittaci or C. trachomatis in the target epithelial cells have pointed to a complete disconnection of chlamydial inclusions from the endocytic pathway and the lack of phagosomal acidi®cation (Heinzen et al, 1996;Schramm et al, 1996;Taraska et al, 1996).…”
Section: Introductionmentioning
confidence: 74%
“…Observations of fusion between chlamydial inclusions that contain microorganisms of the same species but not between inclusions containing di¡erent species [57] have led to the suggestion that the properties of the inclusion membrane of C. psittaci and C. trachomatis (and probably of C. pneumoniae and C. pecorum, too) are di¡erent, and that these properties are positively controlled by the organisms in the inclusion. Zeichner [117] demonstrated that the chlamydial vacuole is di¡erent from other`conventional' vacuoles since the membrane protein composition of C. psittaci-containing vacuoles appears to di¡er from the protein composition of the host cell plasma membrane. He performed polyacrylamide gel electrophoresis on chlamydial vacuoles isolated by dextran gradient centrifugation visualizing 10 major proteins instead of a whole set of the host cell (L cells) cytoplasmic membrane proteins.…”
Section: Composition and Function Of The Chlamydial Vacuole Membranementioning
confidence: 99%
“…Chlamydia can recognize and exploit speci¢c receptor sites on the host cytoplasmic membrane that trigger formation of a type of endosome that normally does not fuse with lysosomes (coated-pit or receptor-mediated endocytosis is not programmed for lysosomal fusion) [23,41,117].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Observations of fusion between chlamydial inclusions that contain microorganisms of the same species but not between inclusions containing different species [57]have led to the suggestion that the properties of the inclusion membrane of C. psittaci and C. trachomatis (and probably of C. pneumoniae and C. pecorum , too) are different, and that these properties are positively controlled by the organisms in the inclusion. Zeichner [117]demonstrated that the chlamydial vacuole is different from other ‘conventional’ vacuoles since the membrane protein composition of C. psittaci ‐containing vacuoles appears to differ from the protein composition of the host cell plasma membrane. He performed polyacrylamide gel electrophoresis on chlamydial vacuoles isolated by dextran gradient centrifugation visualizing 10 major proteins instead of a whole set of the host cell (L cells) cytoplasmic membrane proteins.…”
Section: The Chlamydial Vacuolementioning
confidence: 99%